Reduced RKIP enhances nasopharyngeal carcinoma radioresistance by increasing ERK and AKT activity - Yuan, Li (Oncotarget, 2016)
Raf kinase inhibitory protein (RKIP) functions as a chemo-immunotherapeutic sensitizer of cancers, but regulation of RKIP on tumor radiosensitivity remains largely unexplored. In this study, we investigate the role and mechanism of RKIP in nasopharyngeal carcinoma (NPC) radioresistance. The results showed that RKIP was frequently downregulated in the radioresistant NPC tissues compared with radiosensitive NPC tissues, and its reduction correlated with NPC radioresistance and poor patient survival, and was an independent prognostic factor. In vitro radioresponse assay showed that RKIP overexpression decreased while RKIP knockdown increased NPC cell radioresistance. In the NPC xenografts, RKIP overexpression decreased while RKIP knockdown increased tumor radioresistance. Mechanistically, RKIP reduction promoted NPC cell radioresistance by increasing ERK and AKT activity, and AKT may be a downstream transducer of ERK signaling. Moreover, the levels of phospho-ERK−1/2 and phospho-AKT were increased in the radioresistant NPC tissues compared with radiosensitive ones, and negatively associated with RKIP expression, indicating that RKIP-regulated NPC radioresponse is mediated by ERK and AKT signaling in the clinical samples. Our data demonstrate that RKIP is a critical determinant of NPC radioresponse, and its reduction enhances NPC radioresistance through increasing ERK and AKT signaling activity, highlighting the therapeutic potential of RKIP-ERK-AKT signaling axis in NPC radiosensitization.